1995
DOI: 10.1152/ajpcell.1995.268.5.c1157
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of the beta- and gamma-subunits of the human epithelial sodium channel

Abstract: Amiloride-sensitive Na+ channels are an important component of the Na+ reabsorption pathway in a number of epithelia. Here we report the cloning and characterization of cDNAs encoding two subunits of the human kidney epithelial Na+ channel (beta- and gamma-hENaC). Their predicted amino acid sequences were highly homologous (83-85% identical) to the corresponding subunits reported from rat colon (beta- and gamma-rENaC). Both beta- and gamma-hENaC mapped to human chromosome 16. Northern blot analysis showed high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
129
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(135 citation statements)
references
References 24 publications
5
129
0
1
Order By: Relevance
“…To test this hypothesis, we used an airway cell line (JME cells) that had been extensively passaged and did not express ENaC, which we used to measure nonspecific binding after infection with a lentivirus containing an empty vector. To measure specific binding, we then infected these cells with a lentivirus containing yfp-tagged ␣ENaC, because the ␣ENaC subunit alone has previously been shown to form functional ENaCs, although with a significantly smaller conductance (25,26). Stable ␣ENaC expression was confirmed by Western blotting (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To test this hypothesis, we used an airway cell line (JME cells) that had been extensively passaged and did not express ENaC, which we used to measure nonspecific binding after infection with a lentivirus containing an empty vector. To measure specific binding, we then infected these cells with a lentivirus containing yfp-tagged ␣ENaC, because the ␣ENaC subunit alone has previously been shown to form functional ENaCs, although with a significantly smaller conductance (25,26). Stable ␣ENaC expression was confirmed by Western blotting (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…DNA Constructs-Human ␣ENaC, ␤ENaC, and ␥ENaC were cloned in pMT3 as described previously (39,40). Mutations were generated by site-directed mutagenesis (QuikChange; Stratagene).…”
Section: Methodsmentioning
confidence: 99%
“…The ENaC plays a major role in fluid absorption in the kidney, lung and colon and also constitutes the rate-limiting step for sodium absorption (8,(10)(11)(12); it is a multimer consisting of a, b and g subunits (2,(7)(8)(9). These three subunits have been cloned in rats and humans (6,10,13). Canessa et al (10) reported the structure and function of the b subunit of rat ENaC, and recognized them as important candidate genes for causing Liddle's syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Canessa et al (10) reported the structure and function of the b subunit of rat ENaC, and recognized them as important candidate genes for causing Liddle's syndrome. Subsequently, McDonald et al (13) cloned human b and g subunits, and demonstrated that b human ENaC (hENaC) DNA had an open reading frame of 1920 nucleotides encoding a protein of 640 amino acids with a predicted size of 73 kDa. Clinical investigators have recently demonstrated that some mutations of the cytoplasmic C-termimus of the b or g hENaC cause truncation of a part of the C-terminus, leading to increased activity of the ENaC (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation